Critical Thinking Skills of Sundanese Language Education Students : a Rasch Model Analysis - Marfu'i, Lucky Nindi Riandika; Nurihsan, Juntika; Nurhudaya, NFN; Damaianti, Vismaia Sabariah (Pusat Asesmen dan Pembelajaran, 2021)
The discussion of critical thinking skills concerns several multidimensional things, some of them are individual’s decision making and problem solving skills. Critical thinking skills related to an individual's ability to understand some words or sentences. Students who had a high interpretation skill were likely to have a high critical thinking skill as well. Since some studies had proven that students with language background had a high critical thinking skill, this study was aimed to find whether students with Sundanese language background also had high critical thinking skills. Using quantitative approach, this study investigated the level of critical thinking skills of Sundanese Language Education students in a public University, in Bandung, West Java, Indonesia. The sample in this study was 38 students. This measurement of critical thinking skills uses a test instrument of adolescent critical thinking skills developed by researchers and has moderate reliability. This study used polytomous data, which score range of 0-3 on each item's answer. Based on the results of Scalogram, analyzed using RASCH model, the critical thinking skills of Sundanese Language Education students were in a high category. The validity of this result was shown by the consistency of students in answering questions portrayed in the result of that Scalogram. This finding is allign with several studies that explained that individuals who exceled in language ability and had a high understanding ability, would also have a high critical thinking skill. Some pedagogical implications were also provided in this study.